Cantos de Wirikuta: la ruta de los antepasados y capitalismo extractivo en el lugar donde nació el Sol. - Avilés Conesa, Ángel David (Revista Espanola de Antropologia Americana)
The entry of mining and agricultural companies seeking resources in the Altiplano-Wirikuta region, located in the state of San Luis Potosí (Mexico), and the resulting ecosocial conflict with the local inhabitants and the Wixarika people highlight a significant challenge in the negotiations among the various actors involved. This situation presents us with views that construct the territory from different cultural frameworks, which traditional political practices are not equipped to address. The aim of this work is to reflect on the status of the territory’s reality as processes of power mobilization in crisis contexts triggered by the incursion of the extractivist production model in the Altiplano-Wirikuta.